Predictors for blood loss and transfusion frequency to guide blood saving programs in primary knee- and hip-arthroplasty - Christina Pempe (Nature Portfolio, 2021)
Abstract Endoprosthetic surgery can lead to relevant blood loss resulting in red blood cell (RBC) transfusions. This study aimed to identify risk factors for blood loss and RBC transfusion that enable the prediction of an individualized transfusion probability to guide preoperative RBC provision and blood saving programs. A retrospective analysis of patients who underwent primary hip or knee arthroplasty was performed. Risk factors for blood loss and transfusions were identified and transfusion probabilities computed. The number needed to treat (NNT) of a potential correction of preoperative anemia with iron substitution for the prevention of RBC transfusion was calculated. A total of 308 patients were included, of whom 12 (3.9%) received RBC transfusions. Factors influencing the maximum hemoglobin drop were the use of drain, tranexamic acid, duration of surgery, anticoagulation, BMI, ASA status and mechanical heart valves. In multivariate analysis, the use of a drain, low preoperative Hb and mechanical heart valves were predictors for RBC transfusions. The transfusion probability of patients with a hemoglobin of 9.0–10.0 g/dL, 10.0–11.0 g/dL, 11.0–12.0 g/dL and 12.0–13.0 g/dL was 100%, 33.3%, 10% and 5.6%, and the NNT 1.5, 4.3, 22.7 and 17.3, while it was 100%, 50%, 25% and 14.3% with a NNT of 2.0, 4.0, 9.3 and 7.0 in patients with a drain, respectively. Preoperative anemia and the insertion of drains are more predictive for RBC transfusions than the use of tranexamic acid. Based on this, a personalized transfusion probability can be computed, that may help to identify patients who could benefit from blood saving programs.